2015
DOI: 10.1038/ajg.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Significance of Incomplete Mucosal Recovery in Celiac Disease After 1 Year on a Gluten-Free Diet

Abstract: The presence of more severe disease in terms of histology, serology, and signs of malabsorption was associated with histological non-response. In patients with high dietary adherence, incomplete villous recovery after 1 year does not affect the clinical response or long-term prognosis. A personalized approach is required to decide the optimal timing of the follow-up biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 44 publications
8
78
0
Order By: Relevance
“…Gastrointestinal and psychological symptom scores were no different between cases and controls. Among a cohort of 263 patients who underwent follow‐up biopsy after 1 year on a gluten‐free diet, patients who reported malabsorptive symptoms at the time of initial diagnosis were more likely to have persistent mucosal injury, however gastrointestinal symptoms at the time of follow‐up did not predict histology . Another study compared 42 symptomatic and 27 asymptomatic coeliac disease patients, all on the gluten‐free diet, who underwent follow‐up upper endoscopy .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal and psychological symptom scores were no different between cases and controls. Among a cohort of 263 patients who underwent follow‐up biopsy after 1 year on a gluten‐free diet, patients who reported malabsorptive symptoms at the time of initial diagnosis were more likely to have persistent mucosal injury, however gastrointestinal symptoms at the time of follow‐up did not predict histology . Another study compared 42 symptomatic and 27 asymptomatic coeliac disease patients, all on the gluten‐free diet, who underwent follow‐up upper endoscopy .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to predict the most appropriate time to perform repeat duodenal biopsies in CD, because the rate of mucosal recovery following the institution of a GFD varies between individuals. Some studies suggest that histological remission occurs in most individuals (68%) within the first year following diagnosis [32]. However, other observational studies have reported histological remission in 34-65% of individuals up to two years post-diagnosis, and others have suggested that mucosal recovery may even take as long as 5 years in some individuals [33][34][35][36].…”
Section: Dietary Indiscretionmentioning
confidence: 99%
“…In accord with our previous study [51], for currently unclear reasons, ASCA levels were generally higher in the IgG class than the IgA class. By contrast, IgA class ASCA seems to be more consistently elevated in IBD [48,52]. Which of these two antibody classes is the more useful marker in CD would be an interesting subject for further research.…”
Section: Discussionmentioning
confidence: 96%